Cell-mediated Immunity to Intrinsic Factor in Autoimmune Disorders. Issue 5943 (30th November 1974) - James, D.; Asherson, G.; Chanarin, I.; Coghill, N.; Hamilton, S.; Himsworth, R. L.; Webster, D.
Abstract : Evidence of cell-mediated immunity to gastric intrinsic factor was present in 86% of patients with pernicious anaemia and in at least 13% of patients with hyperthyroidism, 21% of patients with atrophic gastritis, and four out of nine (46%) patients with hypogammaglobulinaemia. Controls gave negative results. The four patients with hypogammaglobulinaemia and cell-mediated immunity to intrinsic factor had evidence of impaired gastric function.